PROFILE OF HEMOSTASIS PHYSICAL DISORDERS IN CONFIRMED COVID-19 PATIENTS TREATED IN THE ISOLATION ICU UDAYANA UNIVERSITY HOSPITAL PERIOD OF 2020-2021 - Indrastuti, Putu Shintadewi; Aryabiantara, I Wayan; Mas Shintya Dewi, Dewa Ayu; Utara Hartawan, I Gusti Agung Gede (E-Jurnal Medika Udayana, 2024)
COVID 19 is contagious disease cause by the Coronavirus which is a type of RNA virus that causes symptoms. In some cases, coagulation disorders have been found as a hemostatic dysfunction that occurs due to a decrease patient's immune system. This condition causes patients to experience coagulopathy, endothelial dysfunction, excessive platelet activation and blood flow stasis. This research used descriptive methods and cross-sectional approach. The population of this study was the Isolation ICU patients at Udayana University Hospital in 2020-2021. Data collection uses PT, aPTT, INR, D-dimer and platelet count data. The results of this study found that out of 169 subjects, the most common cases occurred in the male group at 69.2%, the age group most often occurred in the age > 60 years at 42.6%, based on comorbid group, the most common cases occurred in those with no comorbidities at 37.9% with the most common clinical symptom in the form of shortness breath at 77.5%. The most common picture of coagulation parameters was normal PT values in 55%, a normal INR in 81.1%, an increased APTT in 53.3%, an increased D-Dimer in 91.9%, and normal platelets counts in 69.2%. Coagulation parameters in hypertensive and diabetic mellitus type II patients increased on aPTT sequentially by 50% and 52%, respectively. D-dimer increased in 93% and 98% meanwhile PT, INR and Platelets are normal.